2005
DOI: 10.1109/lsp.2005.843762
|View full text |Cite
|
Sign up to set email alerts
|

On the multiangle centered discrete fractional Fourier transform

Abstract: Existing versions of the discrete fractional Fourier transform (DFRFT) are based on the discrete Fourier transform (DFT). These approaches need a full basis of DFT eigenvectors that serve as discrete versions of Hermite-Gauss functions. In this letter, we define a DFRFT based on a centered version of the DFT (CDFRFT) using eigenvectors derived from the Grünbaum tridiagonal commutor that serve as excellent discrete approximations to the Hermite-Gauss functions. We develop a fast and efficient way to compute the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 18 publications
(35 reference statements)
0
33
0
Order By: Relevance
“…Therefore, for these elliptical rotations an angle modification and a post-phase compensation in the DFRFT are required to obtain results similar to the continuous FRFT [60]. This approach has been extended to the socalled multiple-parameter discrete fractional Fourier transform (MPDFRFT) [65], [66]. In fact, the MPDFRFT maintains all of the desired properties and reduces to the DFRFT when all of its order parameters are the same.…”
Section: Dfrft Based On Eigenvectorsmentioning
confidence: 99%
“…Therefore, for these elliptical rotations an angle modification and a post-phase compensation in the DFRFT are required to obtain results similar to the continuous FRFT [60]. This approach has been extended to the socalled multiple-parameter discrete fractional Fourier transform (MPDFRFT) [65], [66]. In fact, the MPDFRFT maintains all of the desired properties and reduces to the DFRFT when all of its order parameters are the same.…”
Section: Dfrft Based On Eigenvectorsmentioning
confidence: 99%
“…The authors had derived another type of discrete fractional Fourier transform as reported in [13,[18][19][20][21][22][23][24][25] by searching the eigenvectors and eigenvalues of the DFT matrix followed by computing the fractional power of the DFT matrix based on Hermite function. This type of DFRFT worked very similarly to the continuous FRFT, and it fulfills the properties of orthogonality, additivity, and reversibility.…”
Section: Eigenvector Decomposition Type Dfrftmentioning
confidence: 99%
“…Therefore, for these elliptical rotations an angle modification and a postphase compensation in the DFRFT have been required to obtain results similar to the continuous FRFT [24]. This approach has been extended to the so-called multiple-parameter discrete fractional Fourier transform (MPDFRFT) [20,25]. In fact, the MPDFRFT maintains all desired properties and reduces to the DFRFT when all of its order parameters are the same.…”
Section: Eigenvector Decomposition Type Dfrftmentioning
confidence: 99%
“…The target vibration can be estimated through successive chirp-rate estimations using the discrete fractional Fourier transform (DFrFT), which is inherently geared toward chirprate estimation [3], [4], [5], [6], [7]. Later on, a subspace method was incorporated into the DFrFT-based method and it provides better performance than the direct DFrFT-based method in noise [8], [9].…”
Section: Introductionmentioning
confidence: 99%